Clinicopathological features of different Histopathological Subtypes and Stages of Wilms Tumor - Ahmad, Alia; Anjum, Aysha; Hashim, Imran; Hussain, Mahvish; Zaman, Samina; Sahrish, Fariha (Journal of Rawalpindi Medical College, 2023)
Introduction: Wilms tumor is the most common pediatric renal neoplasm. Following preoperative therapy, various histological subtypes, risks and clinical stages are determined as per following SIOP 2001 protocol. To determine the clinicopathological features of different histopathological subtypes and stages of Wilms tumor after completing course of preoperative as well as postoperative chemotherapy following SIOP 2001 protocol. Methodology: This is a retrospective cross-sectional study and sample size calculated by non-probability technique. Ninety-three patients with abdominal masses in the Hematology/Oncology Department were included. After radiological and histopathological diagnosis, four weeks of preoperative chemotherapy, given to patients, followed by partial and radical nephrectomies by surgical team. Specimens received in Histopathology Department grossed and microscopically examined for different post chemotherapy histological subtypes. Further risk categorization and clinicopathological staging in accordance with SIOP 2001, done after completion of treatment. Patients called for yearly follow up for the next five years. Categorical variables are presented as frequencies and percentages. Results: Mean age of ninety-three children was 44.4 months + 30.92with predominance of males (55.9%) and more common in right sided kidney (55.9%). Majority patients completed the entire course of treatment (77.4%). Majority were intermediate risk tumors (76.3%) and most common histological subtype was Mixed Tumor subtype (23.4%). In our study majority, tumors were stage III (48.3%) and patients died due to febrile neutropenia (9.6%) Conclusion: In our study the majority of patients completed the entire course of treatment and relapse was fairly less. Patients lost to follow up after nephrectomy and deaths at home caused by febrile neutropenia were our major challenges.